Toxicity in Organizations: A Sample Study on the Perceived Toxicity in Turkish Academicians - ATASOY, MUSTAFA HAKAN (My University, 2021)
The management styles of the organizations and therefore the managers are undoubtedly an important issue for employees. The behavior of both a high-level manager and top managers affects the sense, mood, and behavior of subordinates. For a long time, leadership research has concentrated too much on perfect, romantic, and “good” forms of leadership, but neglected the aggressive part: the toxic leadership. When the bad management is mentioned, the first thing that comes to mind is a bad manager. Poor management, bad leadership, or dark side of leadership is also referred to as the "toxic leadership" in the literature. In this context, in this study, the "Toxicity in Organizations”, which includes malicious, condescending, and critical styles, was analyzed from various perspective. This study focusing specifically on the toxic leadership, and its characteristics, consists of two main parts. In the first part, literature review of toxic leadership in organizations was determined; in the second part a sample study on the perceived toxicity in Turkish academicians was performed. In addition, arguments, and suggestions were made to prevent toxicity
Keywords: toxicity; leadership; organization; management